Assessing the Climate Commitments of the European Union in Energy Challenges Due to the Russia-Ukraine War 2022 - Siti Zulhaiziah Azalea Zahfira (Universitas Airlangga, 2024)
This research examines the European Union's (EU) climate commitments during the Russia-Ukraine war in 2022. EU as a proactive international organisation in global climate management, has made various efforts through policy and strategy formulation and implementation mechanisms, as well as by playing an important role in international climate negotiations. However, the Russia- Ukraine War has affected the EU's energy security and energy transition agenda. This research uses a qualitative approach and case study analysis method, with secondary data sources obtained through library research collection techniques. To answer the research questions, the conceptual framework of ‘environmental security' is used to analyse the energy response in the EU based on environmental protection considerations, which then illustrates the climate commitments in the EU during the Russia-Ukraine War. The research found that while some of these measures may come at the expense of the EU's climate mitigation efforts in the short term, the EU's overall energy response to avoid an energy crisis in its member states still demonstrates a strong commitment to the fight against global climate change.